Desenvolvimento de um protótipo de aplicações interativas para TV Digital no Middleware Ginga com objetos NCL - Antunes, Marco Aurelio Migliorini [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The Digital Interactive TV (DTV) presents interactivity as a facilitator in the process of interaction where, through it, direct communication with their viewer is possible. Thus, this paper seeks to show the essential foundations and features of the iDTV as local interactivity instrument, analyze its implementation in Brazil and study the forms of interactivity. For this, we intend to demonstrate the development of a prototype application for iDTV middleware Ginga in place with interactivity and NCL objects, which seeks to insert interactivity in a television commercial, with the goal of providing a support tool and additional information to the viewer. It is believed that interaction with iDTV can bring many innovations to the advertising area in the coming years, improving the contact between companies and customers, and may even become a trend in viewing and testing of products. The development of this prototype aims to study the development of the local interactive models easy to use and understand data, providing new possibilities for TV products. To this end, it took some changes while creating the project so that use was facilitated by user as well as the provision of information on the screen to ofter the least harm to the original commercial, as it aims to add information to the viewer

A TV Digital Interativa (TVDi) apresenta a interatividade como um instrumento facilitador no processo de interação onde, através dela, será possível uma comunicação direta com o telespectador. Assim, o presente trabalho procura mostrar os fundamentos e características essenciais da TVDi como instrumento de interatividade local, analisar a sua implementação no Brasil e estudar as formas de interatividade. Para isso, pretende-se demonstrar o desenvolvimento de um protótipo de aplicação para a TVDi no middleware Ginga com interatividade local e objetos NCL, que visa inserir interatividade num comercial televisivo, com o objetivo de oferecer uma ferramenta de apoio e informação complementar ao telespectador. Acredita-se que interatividade com a TVDi pode trazer diversas inovações à área publicitária nos próximos anos, melhorando o contato entre empresas e clientes, podendo até tornar-se uma tendência na visualização e experimentação de produtos. O desenvolvimento deste protótipo, visa estudar a elaboração de modelos de interatividade local de fácil utilização e compreensão de dados, provendo novas possibilidades para produtos televisivos. Para tal, foram necessárias algumas alterações durante a criação do projeto para que a utilização fosse facilitada ao usuário, bem como a disposição das informações na tela oferecessem o menor prejuízo ao comercial original, já que objetiva agregar informações ao telespectador
Applications of a prototype development for interactive digital TV on object Middleware Ginga NCL
Keywords: Televisão digital; Arranjos produtivos locais; Interação homem-maquina; Anúncios em televisão; Publicidade; Digital television